Interval Timing in Pediatric Multiple Sclerosis: Impaired in the Subsecond Range but Unimpaired in the One-Second Range - Troche, Stefan J.; Kapanci, Tugba; Rammsayer, Thomas H.; Kesseler, Carl P. A.; Häusler, Martin Georg; Geis, Tobias; Schimmel, Mareike; Elpers, Christiane; Kreth, Jonas H.; Thiels, Charlotte; Rostásy, Kevin (Frontiers in Neurology, 2020)
Background: For adult multiple sclerosis (MS) patients, impaired temporal processing of simultaneity/successiveness has been frequently reported although interval timing has been investigated in neither adult nor pediatric MS patients. We aim to extend previous research in two ways. First, we focus on interval timing (instead of simultaneity/successiveness) and differentiate between sensory-automatic processing of intervals in the subsecond range and cognitive processing of intervals in the one-second range. Second, we investigate whether impaired temporal information processing would also be observable in pediatric MS patients' interval timing in the subsecond and one-second ranges. Methods: Participants were 22 pediatric MS patients and 22 healthy controls, matched for age, gender, and psychometric intelligence as measured by the Culture Fair Test 20-R. They completed two auditory interval-timing tasks with stimuli in the subsecond and one-second ranges, respectively, as well as a frequency discrimination task. Results: Pediatric MS patients showed impaired interval timing in the subsecond range compared to healthy controls with a mean difference of the difference limen (DL) of 6.3 ms, 95% CI [1.7, 10.9 ms] and an effect size of Cohen's d = 0.830. The two groups did not differ significantly in interval timing in the one-second range (mean difference of the DL = 26.9 ms, 95% CI [−14.2, 67.9 ms], Cohen's d = 0.399) or in frequency discrimination (mean difference of the DL = 0.4 Hz, 95% CI [−1.1, 1.9 Hz], Cohen's d = 0.158). Conclusion: The results indicate that, in particular, the sensory-automatic processing of intervals in the subsecond range but not the cognitive processing of longer intervals is impaired in pediatric MS patients. This differential pattern of results is unlikely to be explained by general deficits of auditory information processing. A tentative explanation, to be tested in future studies, points to subcortical deficits in pediatric MS patients, which might also underlie deficits in speech and visuomotor coordination typically reported in pediatric MS patients.